PENGEMBANGAN POTENSI HUTAN BAKAU TANJUNG BATU DESA SEKOTONG TENGAH MELALUI WISATA BERBASIS EVENT DAN EKOWISATA KONSERVASI - Hakim, Arif Al; Yuzila, Baiq Yayit; Yuandana, Gent; Mir’atillah, Insani; Nurfajrin, Nurfajrin; Rizqiah, Pelita; Fitri, Rizka Aidatul; Ulyana, Siska; S., Tirangga Jundhi Jayeng A.; Putri , Uswatun Desiana (Universitas Mataram, 2023)
Sekotong Tengah Village has a mangrove forest area of 11 hectares and is one of the tourism potentials that can be developed, one of which is through the Tourism Village Thematic KKN program. The implementation of the Tourism Village KKN Program in Sekotong Tengah Village focuses on mangrove forest conservation through efficiency efforts from reducing energy, production, transmission, or distribution as an effort to protect and manage the environment and its coastal natural resources that are expected to be able to make Sekotong Tengah Village a sustainable ecotourism-based tourism villages. In addition, through event-based tourism promotion activities it is also hoped that it will help the community's self-sufficiency to continue to innovate with their tourism potential, be able to restore the economy after the covid-19 pandemic, increase awareness of natural functions, ability to recognize coastal potential, and organize natural resources and community resources to create a tourist village. These things have been able to increase public awareness of the tourism potential they have so this has encouraged public awareness to continue to innovate with the potential they have, able to increase the existence of the Tanjung Batu mangrove forest tourism area, and have an impact on improving the economy of the community around the post-pandemic area Covid-19.